Spiritual Practices in The Era of Smartphones & Social Networking: A Comparative Study - Monterosso, Daniele Maria; Kumar, Vikas; Zala , Kalpesh (International Journal of Psychosocial Rehabilitation, 2018)
Nowadays, it is commonly observed that with the advancement of mobile phones, there is an increase in the number of mobile phone users, especially young adults or adolescents. They are using mobile phones very frequently for day to day activities. Keeping in view this thing, it is important to study the relationship between spiritual practices and smartphone & social networking addiction among undergraduate students. The paper will explore the coexistence of spiritual practice and social media plus smartphone usage of adolescent students. The study was conducted on a sample of 110 adolescent students of Sri Sri University Cuttack. Mobile Phone Addiction Scale developed by Dr. A. Velayudhan and Dr. S. Srividya and Social Networking Addiction Scale by Dr. Nivedita Baungoli were used for data collection. The researcher selected the sample of 110 youth out of which, 55 were non-spiritual practitioners and 55 were spiritual practitioners. The main findings indicated it is very intriguing to discover that student that is in spiritual practices have shown a higher level of addiction in relation to students who do not practice. This could be because the students who practice any form of spiritual practices are having more energy thus, if not channelize properly it may lead to mobile or social networking addiction.